m → 0 lim m 1 ∫ 2 π 2 π + m cos ( x 2 ) d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
@Chew-Seong Cheong please explain how it is a 0/0 case?
Log in to reply
Note that m → 0 lim ∫ a a + m f ( x ) d x = 0 and m → 0 lim m = 0 . I missed out the m 1 earlier.
Problem Loading...
Note Loading...
Set Loading...
L = m → 0 lim m 1 ∫ 2 π 2 π + m cos ( x 2 ) d x = m → 0 lim 1 cos ( ( 2 π + m ) 2 ) = 1 cos ( 2 π ) = 0 A 0/0 case, L’H o ˆ pital’s rule applies. Differentiate up and down w.r.t. m .
Reference: L'Hôpital's rule